Pengaruh Cause Related Marketing, Corporate Image, dan Customer Satisfaction terhadap Purchase Decision pada Produk Blue Bag IKEA di Bandung - Moch Luthfan Sopianda; Dedy Ansari Harahap; Moch. Malik Akbar Rohandi (UNISBA Press, 2023)
Abstract. The purpose of this study was to find out how cause related marketing, corporate image, customer satisfaction and consumer purchasing decisions on the IKEA blue bag product are described and to find out how cause related marketing, corporate image and consumer satisfaction influence purchasing decisions. This research is a descriptive and verification research with quantitative methods. The sampling technique used is nonprobability sampling, namely purposive sampling. The population in this study were consumers who had visited IKEA and purchased blue bag products and a sample of 195 people were obtained. Data analysis used is descriptive and verification analysis using multiple linear regression analysis, F test, t test, and the coefficient of determination. The results of this study indicate that the cause-related marketing variables partially do not have a significant effect on purchasing decisions, company image variables partially influence purchasing decisions, and customer satisfaction variables partially have a significant effect on purchase decisions. And simultaneously cause related marketing variables, corporate image, and consumer satisfaction have a significant effect on purchasing decisions on IKEA blue bag products in the city of Bandung. Abstrak. Tujuan penelitian ini adalah untuk mengetahui bagaimana gambaran cause related marketing, corporate image, customer satisfaction dan purchase decision pada produk blue bag IKEA serta untuk mengetahui bagaimana pengaruh cause related marketing, corporate image dan customer satisfaction terhadap purchase decision. Penelitian ini merupakan penelitian deskriptif dan verifikatif dengan metode kuantitatif. Teknik sampling yang digunakan adalah nonprobability sampling yaitu purposive sampling. Populasi pada penelitian ini adalah konsumen yang sudah mengunjungi IKEA dan melakukan pembelian produk blue bag dan didapatkan sampel sebanyak 195 orang. Analisis data yang digunakan adalah analisis deskriptif dan verifikatif menggunakan anlisis regresi linier berganda, uji F, uji t, dan koefisien determinasi. Hasil dari penelitian ini menunjukan bahwa variabel cause related marketing secara parsial tidak berpengaruh signifikan terhadap purchase decision, variabel corporate image secara parsial berpengaruh terhadap purchase decision, variabel customer satisfaction secara parsial berpengaruh signifikan terhadap purchase decision. Dan secara simultan variabel cause related marketing, corporate image, dan customer satisfaction berpengaruh signifikan terhadap purchase decision pada produk blue bag IKEA di kota bandung.